PENGEMBANGAN APLIKASI SIMBA (SISTEM INFORMASI MITIGASI BENCANA) SEBAGAI MEDIA PELAYANAN INFORMASI RAWAN BENCANA KABUPATEN GUNUNGKIDUL - Nur Samsu (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2021)
The development of SiMBa aims to build a disaster mitigation support system based on a Geographic Information System with an open-source platform in processing, creating, and disseminating disaster maps (maps of risk, hazard, and vulnerability) as well as recording disaster events in Gunungkidul Regency. The methodology used in this development is Feature Driven Development (FDD) so that progress can be carried out in a simple and short period. The development of SiMBa concludes that the use of the open-source platforms that were developed can be used as a platform for the application of technical standards in disaster-prone information services in fulfilling Minimum Service Standards (SPM) in Sub-Disaster Affairs. SiMBa is expected to support the assessment of the Regional Resilience Index (IKD) and the Indonesian Disaster Risk Index (IRBI) which specifically target strategies on priorities 2, 3, 4, and 6 in the capacity index improvement strategy in Gunungkidul Regency, Indonesia